May-June 2023 California Current Fast Repetition Rate Fluorometer (FRRF) Data - Yayla Sezginer; Philippe Daniel Tortell (PANGAEA, 2025)
Continuous phytoplankton physiology measurements were collected with an FRRF onboard the R/V Sally Ride during the Phytoplankton UPwelling Responses (PUPCYCLE) Expedition II, which took place from May 27 - June 12, 2023 on a transit between Newport, OR and San Francsico, CA. The ship extquotesingles seawater supply line with an intake depth of ~5m delivered seawater to a Soliense Inc. FRRF configured for autonomous operation. A peristaltic pump integrated into the FRRF instrument was used to flush the instruments sample cuvette for 2.5 minutes before introducing a fresh sample. Samples were held in the dark for 1 minute of dark acclimation before collecting 5 dark measurements and 5 light measurements under an actinic irradiance of 150 micromol photons per m2 per second. Continuous sampling was interrupted every three hours to run a photosynthesis-irradiance measurements. During the photosynthesis-irradiance sequence, a single sample was isolated in the cuvette and analyzed under eleven increasing actinic light steps ranging from 0 - 850 micromol photons per m2 per second. Actinic light was evenly supplied by five LED lamps with wavelengths of 445, 470, 505, 530, and 590 nm. All excitation light pulses were delivered by the 445 nm lamp. For further details on the Fast Repetition Rate Fluorometry method see Schuback et al., 2021 (doi:10.3389/fmars.2021.690607). For full description of the biophysical model, see Kolber et. al., 1998 (doi:10.1016/S0005-2728(98)00135-2). Anyone wishing to reprocess this data should please contact Yayla Sezginer (ysezginer@eoas.ubc.ca) who collected this data and can provide further details.